2014
DOI: 10.1109/tap.2014.2356208
|View full text |Cite
|
Sign up to set email alerts
|

Rain Attenuation Prediction Model for Satellite Communications in Tropical Regions

Abstract: This paper proposes a model for predicting rain attenuation in the tropical region. Slant path rain attenuation measurements were carried out in Singapore by analyzing the beacon signals from two satellites, namely WINDS and GE23, operating at frequencies of 18.9 and 12.75 GHz respectively. Rainfall rates at the location of the beacon receivers were recorded. The cumulative distributions of the rainfall rate and the corresponding rain attenuation are presented and analyzed. It is found that the cumulative dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 23 publications
0
30
0
Order By: Relevance
“…Figure shows the comparison of the predicted diversity gain between Matricciani's model derived for Spino, Italy and our proposed model derived for Japan determined from the frequency‐dependent coefficients of time delays in Table and from Equation . The results in Figure (a) and (b) show that Matricciani's model overestimates and it gives more error than our proposed model, for example, at 10 min delay prediction, Matricciani's model error is 0.894 but our proposed model error is 0.256 and other quantitative errors are shown in Table .…”
Section: Simulation Resultsmentioning
confidence: 99%
“…Figure shows the comparison of the predicted diversity gain between Matricciani's model derived for Spino, Italy and our proposed model derived for Japan determined from the frequency‐dependent coefficients of time delays in Table and from Equation . The results in Figure (a) and (b) show that Matricciani's model overestimates and it gives more error than our proposed model, for example, at 10 min delay prediction, Matricciani's model error is 0.894 but our proposed model error is 0.256 and other quantitative errors are shown in Table .…”
Section: Simulation Resultsmentioning
confidence: 99%
“…However, the efficiency of these techniques in guaranteeing optimal performance of the network in the utilization of allocated resources as well as satisfaction of the QoS requirements of accepted connections is directly related to the accuracy with which the dynamics of rain attenuation are perceived. Prediction-based models of rain events have been developed and are employed to predict the rain attenuation on satellite links [2][3][4]. Based on these models, various techniques are developed to efficiently mitigate the rain attenuation experienced by users.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown several models rain attenuation prediction for satellite communication systems, for example, Recommendation ITU-R P.618-13 [2], Ramachandran-Kumar model [3], Yeo-Lee-Ong model [4] and Rakshit-Adhikari-Maitra model [5]. These models depend on rain rate, R, so accuracy in predicting rain attenuation is mainly related to whether or not rain measurements exist in the locality of interest.…”
Section: Introductionmentioning
confidence: 99%